Community paramedicine program and outcomes of referred coronary artery bypass grafting patients - Regan Washist; Casey Smith; Tyler Kientopf (James Cook University, 2024)
Introduction: Community paramedicine is a field in its infancy. The use of community paramedics has expanded in recent years as an alternative or adjunct to home health in the continued drive to decrease health disparities and complications. In current practice, they function in a position like a home healthcare nurse with an expanded scope of practice, such as providing specialized follow-up care, for example with postoperative care for patients who have undergone major surgery or recent hospitalization. This study assesses if community paramedics are a valid option in reducing rehospitalization of patients who underwent a coronary artery bypass grafting (CABG) procedure. Methods: A retrospective chart review between 2021 and 2022 was performed on all patients who underwent CABG in Bismarck, North Dakota, along with obtaining a referral for the community paramedics spanning urban and rural areas. A comparison was made between individuals who saw the community paramedics in their post-care versus those who continued with the standard of care. Results: There were 80 participants and 38 location-matched controls. All variables were found to be statistically insignificant except for the number of walk-in visits (urgent care), in which 7 out of 38 sought medical attention in the controls and 4 out of 80 sought medical attention in the participants. The proportions of inpatient readmission rates and emergency department (ED) visits were similar. Discussion: Given that paramedicine is in its infancy, the emergence of other variations of the community paramedic certification has brought a discussion of their scope of practice. While walk-in visits, even with the limitations, showed significant improvement with the addition of community paramedics, more research is still needed to show their effectiveness in reducing readmission to hospital. Additionally, the patients who sought help from community paramedics may be more likely than the controls to seek help from medical professionals. Conclusion: This study provided a novel look into the effect that community paramedics can have on patients in urban and rural areas in regard to reducing postoperative complications and minimizing unnecessary advanced healthcare utilization.